분사압력 변화에 따른 디젤-DME연료의 다단분사 특성에 관한연구 - 정연호; Y. H. Jeong; 양지웅; J. W. Yang; 오충환; C. H. Oh; 임옥택; O. T. Lim (한국분무공학회지, 2013)
An investigation on spray characteristics of fuels which diesel and di-methyl ether (DME) with change of injection pressure used the multi-injection in constant volume combustion chamber (CVCC). Diesel was already used famous fuel which we could use. DME showed similar features with diesel like as cetane number, auto-ignition temperature. High cet-ane number of diesel and DME could make possible to compression ignition. DME showed different atomization hom diesel due to evaporating pressures and boiling points. Experiments were carried out in CYCC equipped with Delphi sole-noid 6-hole type injector and the spray characteristics of diesel and DME were tested the various pre and pilot injection. Terms of injections and a number of injections in multi-injection has been controlled. Experiments were perfonned in 2 types that 1500 rpm, 2000 rpm and under the condition of injection ranging from 100 bar to 500 bar. From the results of this experiment diesel showed longer spray penetration than DME. That result showed dilferent of atomization speed DME and diesel. Result of high injection pressure condition showed similar spray characteristics diesel and DME. After this investigation, new conditions and experiments using laser light to go forward and add the Riels like as the biodiesel and diesel and DME blend.